The antidepressant- and anxiolytic-like effects of resveratrol: Involvement of phosphodiesterase-4D inhibition. (15th July 2019) - Zhu, Xia; Li, Wenhua; Li, Yongkun; Xu, Wenhua; Yuan, Yirong; Zheng, Victor; Zhang, Hanting; O'Donnell, James M.; Xu, Ying; Yin, Xiaoxing
Abstract: Resveratrol is a natural non-flavonoid polyphenol found in red wine, which has numerous pharmacological properties including anti-stress and antidepressant-like abilities. However, whether the antidepressant- and anxiolytic-like effects of resveratrol are related to the inhibition of phosphodiesterase 4 (PDE4) and its subtypes remains unknown. The same holds true for the subsequent cAMP-dependent pathway. The first set of studies investigated whether resveratrol exhibited neuroprotective effects against corticosterone-induced cell lesion as well as its underlying mechanism. We found that 100 μM corticosterone induced PDE2A, PDE3B, PDE4A, PDE4D, PDE10 and PDE11 expression in HT-22 cells, which results in significant cell lesion. However, treatment with resveratrol increased cell viability in a dose- and time-dependent manner. These effects seem related to the inhibition of PDE4D, as evidenced by resveratrol dose-dependently decreasing PDE4D expression. In addition, the PKA inhibitor H89 reversed resveratrol's effects on cell viability. Resveratrol prevented corticosterone-induced reduction in cAMP, pVASP(s157), pCREB, and BDNF levels, indicating that cAMP signaling is involved in resveratrol-induced neuroprotective effects. Not to mention, PDE4D knockdown by PDE4D siRNA potentiated the effect of low dose of resveratrol on cAMP, pVASP, pCREB, and BDNF expression, while PDE4D overexpression reversed the effect of high dose of resveratrol on the expression of the above proteins. Finally, the subsequent in vivo data supports the in vitro findings, suggesting that resveratrol-induced antidepressant- and anxiolytic-like effects are mediated by PDE4D. Overall, these findings support the hypothesis that PDE4D-mediated cAMP signaling plays an important role in resveratrol's protective effects on stress-induced depression- and anxiety-like behavior. Highlights: The neuroprotective effects of resveratrol in vitro or in vivo were investigated. The increases of PDE4D in the hippocampus led to depression- and anxiety-like behavior. PDE4D-mediated cAMP signaling may play an important role in resveratrol's protective effects in stressed mice.